Reconsidering the fear of God in the wisdom literature of the Hebrew Bible in the light of Rudolf Otto's "Das Heilige" - Ellis, Ettienne (Old Testament essays, 2014)
This article offers an attempt to discern the extent to which Rudolf Otto's points of view, specifically the idea of "the holy" as the mysterium tremendum, influenced scholarly opinion on the meaning and significance of the fear of God in the HB in general and in the wisdom literature in particular. It is found that Otto did indeed have a great influence on the understanding of the meaning of the fear of God, but that scholars also allowed their opinions to be guided by a competent analysis of the different nuances that the fear of God takes on in the biblical text itself. The findings lead to the conclusion that scholars should recognise both the possibilities and the limitations of Otto's views in any attempt to delineate the meaning and significance the fear of God in the HB.